The red blazer girls the ring of Rocamadour - Beil, Michael D. (Yearling, 2009)
Catholic-schooled seventh-graders Sophie, Margaret, Rebecca, and Leigh Ann help an elderly neighbor solve a puzzle her father left for her estranged daughter twenty years ago